Study of Comet Tail Interactions with Solar Wind Using MHD Based Model - Khalaf, Salman (Iraqi Journal of Science, 2025)
In the present work, the different possible interactions between comet tail and the solar wind in the present of the inter-planetary magnetic field (IMF) had been studied. Magneto-hydrodynamic laws (MHD) were used to simulate interactions occurring between comet tail and solar wind using one –dimensional space. The model simulation was achieved using Lax-Wendroff explicit method. The interaction between cometary tail ions and solar wind can be understood by means of spatial distribution of new-generated ions from the comet nucleus with the homogenous flow of the solar wind plasma. The difference between average molecular mass of both types along with step-increase in the number of particles can reproduce the whole shape of the comet tail, thus comparison the results of the MHD simulation can be mode fruitful to understand the specific type of particles interaction. The results show that the molecules weight distributes in such away that fallows the direction of the IMF and decreases rapidly as the distance increases away from the nucleus. Pressure results indicate that the velocity of the particles around the nucleus must decrease. That was explained on the bases of mass conservation laws. Also the effects of the IMF were explained.